Smallholder Palm Oil for Sustainable Livelihoods in Rural Zambia - C. P. Kapembwa; I. K. Kalunga; Ravindra C. Joshi (Oil Palm Research and Review, 2021)
Cultivation of the palm oil has expanded tremendously in recent years such that it is now competing with crops such as, sunflower, groundnuts, cotton and soybean as a major source of the Zambia’s supply of oils and fats. Presently, Luapula Province in the north is the dominant region of traditional and small older production with Muchinga Province in the north east being the leading industrial producer of palm oil. This article reviews the various factors that have led to palm oil occupying its present position, including traditional and industrial systems, technical, managerial, environmental, and socio-political aspects. Traditional and industrial features recognized as critical to the high productivity of the crop are explained. These include its traditional and industrial production and uses.